Impact of Intercropping Lemon Grass (Cymbopogon citratus Stapf.) on Infestation of Eggplant Fruit and Shoot Borer (Leucinodes orbonalis Guenee) in Eggplant (Solanum melongena L.) - Calumpang, Susan May F.; Bayot, Rolando G.; Vargas, Daniel G.; Ebuenga, Melvin D.; Gonzales, Pablito G. (Silliman Journal, 2022)
The impact of vegetation diversity through intercropping was assessed for its ability to reduce the infestation of eggplant fruit and shoot borer (EFSB), (Leucinodes orbonalis Guenee) on eggplant (Solanum melongena L.) inasmuch as insecticide use in eggplant production is quite heavy. The eggplant-chives-lemon grass cropping system did not give rise to EFSB damage. The population dynamics of insect pests and natural enemies in this mixed eggplant-herbs organic garden showed flea beetles, leafhoppers and mealy bugs while beneficial insects included ants, spiders and coccinellid beetles. In a follow-up study for two consecutive years, the effect of intercropping eggplant with lemon grass on pests populations and yield was compared with farmers’ practice of insecticide use in small plot field trials at the Central Experiment Station, College of Agriculture, UP Los Baños. Eggplant intercropped with lemon grass had lower average leafhopper and aphids but there was no difference for whitefly populations compared to the monocrop. Percentage shoot damaged by EFSB in eggplant intercropped with lemon grass was significantly lower than the monocrop at 9 and 10 weeks after transplanting, although chemical control had the lowest damage. The average weight of eggplant fruit was highest for eggplant intercropped with lemon grass. Total yield in terms of number and weight of marketable fruits was significantly higher in the intercropped plots than in eggplant monoculture and farmers’ practice. To elucidate the operative mechanism in the field, damage potentials and host finding behavior of EFSB in the presence of eggplant and lemon grass were investigated in the laboratory using choice and no-choice cage bioassays. A significant decrease was observed in the number of moths alighting on eggplant with lemon grass, compared to eggplant alone at 24 h after introduction. The average percent shoot damage per plant for the 1:1 eggplant-lemon grass combinations was significantly lower than eggplant alone. Our field and laboratory trials demonstrate repellency effects of intercropping lemon grass with eggplant which has the potential to reduce insecticide use in eggplant production as well as increase income of farmers.